THE CURRENT STATE OF THE SENSORY PROFILES OF UKRAINIAN RED DRY TABLE WINES FROM EUROPEAN GRAPE VARIETIES AND HYBRIDS IN THE CONDITIONS OF CLIMATE CHANGE - LARIN, VITALII; TKACHENKO, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The quality of grapes depends on the climatic characteristics of different regions. Grape varieties and production style significantly affect the differences between wines. the formation of sensory profiles of various grape varieties and regions are current topics of world research. The status of sensory profiles in the context of climate change is also an important area of current research. This work presents the results of the research of production and consumption of dry red table wines in Ukraine and creation of the sensory profiles of Ukrainian red dry table wines from European grape varieties and hybrids in the conditions of climate change. In this study, wines from grapes grown in Transcarpathian, Lviv, Chernivtsi, Vinnytsia, Zhytomyr, Odessa, Mykolaiv, and Kherson regions were selected. The study according to the sensory profiles of Pinot Noir, Merlot, Cabernet Sauvignon, Zweigelt, Cabernet Franc, Cabernet Cortis grape varieties regions are presented. The descriptive-profile method with a 7-point scale and a sensory analysis consensus table was used. The samples were evaluated by the intensity of the aroma groups: floral, fruity, spicy, and aging. In addition, the following taste parameters were evaluated: intensity, acidity, sweetness, aftertaste, and tannins. The sensory profile of the Ukrainian red table wines from the Pinot Noir grape variety determined dominant fruit aromas (4,50) and spices (3,38), acidity (4,25), tannins (3,5) and aftertaste (3,5). The sensory profile of the wines from Cabernet Sauvignon grape variety are characterised by dominant fruit aromas (4,25) and spices (2,33) and aging (1,42), acidity (3,67) and tannins (3,17). These data can be a starting point for determining the sensory profiles of Ukrainian dry red table wines from European grape varieties and hybrids in climate change conditions from different regions and even localities. In addition, the obtained data can be used to improve the sensory profiles of commercial wines from the respective grape varieties.
Keywords: wine; red wine; descriptor; sensory profile; climate change